Transitivity Analysis in Narrative Writing of Grade 9 Students of Junior High School - Budi, Firgiawan Setia; Rahmawati, Istiqomah Nur; Rini, Yulan Puspita (Institut Agama Islam Negeri Palopo, 2024)
This study aims to analyze narrative texts written by 9th-grade students using transitivity analysis. The subjects were selected by several teachers who believed the class was suitable for the study based on their perspectives. Out of the 32 students involved, only 14 wrote narrative texts that met the established criteria. The remaining texts included 6 recount texts, 11 descriptive texts, and 1 procedural text. The transitivity analysis of the 14 narrative texts revealed that students utilized various processes, including material, mental, and relational processes, with a noticeable dominance of material processes. The results of this study revealed that although students could write narrative texts, there were still variations in the use of incomplete generic structures and less varied language features. This can be seen in the results of the transitivity process percentage, material processes showed a rate of 52%, mental processes (22%), verbal processes (8%), behavioral processes (5%), relational processes (12%), and existential processes (1%). These results do not indicate that students' writing follows the grammatical features that apply to narrative texts, where material and mental processes dominate. This study provides insight into students’ narrative writing skills and the use of transitivity in their writing. It provides a basis for developing more effective curriculum and instructional strategies in teaching narrative text in grade 9. The study also identified several limitations, including the limited sample size and manual analysis, which may affect the generalizability of the findings. Recommendations for further research include the use of linguistic analysis software and expanding the research sample.